O peão e o acidente de trabalho na construção civil do Rio de Janeiro: elementos para uma avaliação do papel da educação nas classes trabalhadoras - Klausmeyer, Maria Luiza Cristolaro (1988)
This dissertation seeks to identify specifications bu which the Subsection cf Buildings c f the Civil Construction os Rio de Janeiro could be improved. It attempt to determine the factors that make construction workers both victims of accidents, as well as the cause of these accidents. It a150 seeks t o identify the means af the capitalist way that as the producer specific kind af society, creates this type af invisible of a worker. Further more, to verify the violent ar disguised ways, that lead the worker to have a guilty consclence relative to himself and to the other workers , and maklng him feel responsible even for accident - related deaths on the job. A revolting factor is that malnutrition and endemic hunger, are in large part responsible for accidents at work in the capitalist production system, ln which production relations are still primitive. Therefore, the accidents at work are a product of society, especially caused by conditions in the construction sector . This fac 19 often masked, and responsibility is put on the worker ln 77,5~ of work related accident . Under these specific working conditions the cumulative overtime hours of work and tasks make the rythm and working hours extreme and overburdensome. The large and modern firms subcantract to smoller construc~i ns firms who have more dangeraus working condictions which result in more frequent and mayor accidents. These are not computed in the statistics of the large firms and the workers of the subcontractors do not appear on the builging construction lists, and are therefore a non - existent entities. Even opressed, the workers still continue to work under these conditions mak1ng there resistence a form af struggle. The Education that intends to be transformed in to an instrument of the workers struggle, should stimulated the participation in the daily educational and political practices and try to reconstructed what the dominant knowledge has fragmented: the ptoduction of existence as an integrated whole.